MITIGATION OF HEAT STRESS IN POTATO THROUGH CALCIUM NUTRITION - Rawal, Sanjay; Rana, N S; Kumar, Devendra (Potato Journal, 2013)
Application of supplemental calcium (0, 80, 160, 240 kg ha-1) through gypsum in sandy loam soils resulted in improved cell membrane thermo-stability in potato cultivar Kufri Surya. The growth parameters (leaf number plant-1 and leaf/stem ratio) were not significantly affected, and the tuber and biological yields remained at par with control up to 60 DAP. However, at 75 DAP improved tuber yield (229 g plant-1) and biological yield (333 g plant-1) were recorded at 80 kg Ca ha-1 over control (181 and 262 g plant-1, respectively). The study suggests that Ca treated plants were better equipped to mitigate heatstress.